Rapid Single-Cell Microbiological Analysis: Toward Precision Management of Infections and Dysbiosis. (December 2019) - Li, Hui; Morowitz, Michael; Thomas, Neal; Wong, Pak Kin
Bacterial infection is a leading cause of morbidity and mortality (from infants to the elderly) and accounts for more than 20 billion in healthcare costs in the United States each year. The pathogens responsible for many of the common infectious diseases, such as urinary tract infection (UTI) and ventilator-associated infections (VAIs), have proven to be highly adept in acquiring mechanisms of antimicrobial resistance. The use of broad-spectrum antibiotics by healthcare providers and the infiltration of antibiotics in the environment have accelerated the selection and growth of resistant pathogens. To further exacerbate the problem, the need for new antibiotics has far outpaced the development of new classes of antibiotics by the pharmaceutical industry (only two new classes of antibiotics have reached the market in the last 20 years), in large part due to prohibitive cost and historically poor return on investment to develop new antibiotics. Consequently, clinicians have limited treatment options, particularly in the neediest patients. To tackle this major global health issue, we are developing novel technological approaches for rapid definitive clinical microbiological analysis. These technologies will improve the clinical management of bacterial infections and reduce the improper use of antibiotics in current practice, hopefully limiting the spread of drug-resistant organisms.